Правове регулювання тимчасового обмеження права громадян на виїзд із Республіки Білорусь - Чумак, В. В.; Chumak, V. V.; ORCID: http://orcid.org/0000-0002-6171-2250 (Право і безпека. - 2013. - № 4 (51). - С. 64-70., 2013)
Проаналізовано нормативно-правові акти, які регулюють адміністративно-правовий режим виїзду з Республіки Білорусь та в’їзду до Республіки Білорусь. Встановлено, що адміністративно-правовий режим виїзду з Республіки Білорусь і в’їзду до Республіки Білорусь представляє собою сукупність нормативно-правових актів Республіки Білорусь, що регламентують правила виїзду з Республіки Білорусь і в’їзду до Республіки Білорусь громадян Республіки Білорусь. Визначено правові підстави щодо тимчасового обмеження у праві громадян на виїзд із Республіки Білорусь.

This article is stating, that the administrative and legal regime of entry and departure from the Belarus Republic is a set of normative legal acts, which regulates exit and entry into the Belarus Republic of citizens of the Republic, as well as activities of public authorities and officials on carrying out their organizational and management measures, necessary to ensure the functioning of this regime. The basic grounds for the temporary restriction of the right of citizens to travel to the Republic of Belarus: – If a person familiar with the information constituting a state secret – before the deadline specified in the agreement on access to state secrets; – If a person is a suspect or accused in a criminal case – for a period established by the prosecution, but no more than the cessation of criminal prosecution or till the sentence of the court becomes final; – If the person is convicted of an offense except convicted without punishment or the penalty of deprivation of the right to occupy certain positions or engage in certain activities – for the period prescribed by authority or body, performing penalties or other measures of criminal responsibility, but not more than to sentence or release from punishment or before the expiry of suspended sentence or probation; – If a preventive supervision is established over the person – till the cessation of preventive supervision; – If person fails to comply without good cause property, tax or other obligations to Belarus, its administrative-territorial units, individuals and legal entities, established and entered into force by court orders or executive documents – for the period prescribed by the court, but no more than to fulfill obligations; – If person filed a civil action in court – for the period, prescribed by the court, but not longer than the end of the proceedings; – If person is a debtor in a case of economic insolvency (bankruptcy) or interested party against a debtor-legal entity – from the opening of bankruptcy proceedings for a period set by the court, but not longer than the end of proceedings on economic insolvency (bankruptcy); – If a person evades appearance on measures to conscription or reserve – till appearing of measures to conscription or reserve; – If the person is on preventive register in the state security of Belarus Republic – till the lifting of preventive account.

Проанализированы нормативно-правовые акты, регулирующие административно-правовой режим выезда из Республики Беларусь и въезда в Республику Беларусь. Установлено, что административно-правовой режим выезда из Республики Беларусь и въезда в Республику Беларусь представляет собой совокупность нормативно-правовых актов Республики Беларусь, регламентирующих правила выезда из Республики Беларусь и въезда в Республику Беларусь граждан Республики Беларусь. Определены правовые основания для временного ограничения в праве граждан на выезд из Республики Беларусь.
Чумак, В. В. Правове регулювання тимчасового обмеження права громадян на виїзд із Республіки Білорусь / В. В. Чумак // Право і безпека. - 2013. - № 4 (51). - С. 64-70.
Keywords: Адміністративне право та процес. Адміністративна діяльність. Administrative Law and Procedure. Administrative Activity. Административное право и процесс. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; адміністративно-правовий режим; Республіка Білорусь; право громадян на виїзд; виїзд; административно-правовой режим; временное ограничение прав; тимчасове обмеження прав; Республика Беларусь; право граждан на выезд; выезд; administrative and legal procedures; temporary restriction; Belarus Republic; right of citizens; departure; Білорусь; Беларусь